Penggunaan Aplikasi Michat Sebagai Sarana Prostitusi Online Di Kota Bandung - Dzaky Muhammad Baihaqi; Qisthy Rabathy (KOMVERSAL, 2023)
This study aims to determine the motives, actions and meanings of the use of online prostitution in the city of Bandung. In this research uses qualitative research methods, and using phenomenological theory by Alfred Schutz with data collection techniques used are library research, field observations and in-depth interviews with informants. The results of this study indicate that there are similarities and differences between the informants. Like the motives of MiChat users, which are divided into two, namely sex workers and service users, for sex workers the motive for using MiChat is driven by economic factors and the influence of friends, while for users it is influenced by curiosity, the desire to have sex, and also environmental influences.